Purificación de ADN metagenómico a partir de consorcios bacterianos biodegradables de petróleo crudo. Loreto - Perú - Del Aguila Ríos, Marjorie Tatiana (2022)
Metagenomic DNA purification is the first step to deciphering the genetic information through metagenomic analysis of petroleum biodegrading bacterial consortia. This type of molecular analysis is fundamental to help solve the hydrocarbon contamination problems of soils and rivers in the Peruvian Amazon. The general objective of the present investigation was to purify metagenomic DNA from crude petroleum biodegrading bacterial consortia from the Loreto region. First, petroleum biodegrading bacterial consortia were obtained from soil samples from the Allpahuayo Mishana National Reserve (RNAM) and from the waters of the Itaya and Nanay rivers. To obtain these bacterial consortia, the samples were cultured for 10 days in Bushnell Haas (BH) medium supplemented with 1% crude petroleum and then three consecutive subcultures (in BH medium + 1% petroleum) were performed every 10 days totalling 40 days of culture. Then, metagenomic DNA was purified from the bacterial consortia and evaluated its quality and quantity using standardized methods. Petroleum biodegrading bacterial consortia were successfully obtained from both soil and water samples. These consisted of Gram-positive and Gram-negative cocci, bacilli, coccobacilli bacteria. Moreover, metagenomic DNA obtained from the bacterial consortia was characterized by its purity, high quality, and quantity. In conclusion, the standardized protocol allowed us to get from the bacterial consortia pure metagenomic DNA of high quality and quantity appropriate for studies at the molecular level.